Russian intelligence files on Asia. (Leiden, The Netherlands)
1 mikrofilm makarası (331 poz)
Keywords: Information about Japanese armed forces and about the internal political situation in the country. Geographical and military topographical materials: maps of Japan and its islands, plans of town, ports and harbours, route and road maps.